Determinan Struktur Modal: Bukti Empiris pada Perusahaan Sektor Basic Materials di Indonesia - Sukma Nuraisyah, Reza; Meidiaswati, Harlina (Seminar Nasional Manajemen, 2026)
Capital structure, which is the ratio of total debt to total assets, is a concern for many companies. Increasing debt can increase financial risk if the company fails to meet its fixed interest payments. This study aims to explore the effect of sales growth, non-debt tax shields, tangible assets, and cash flow volatility on the capital structure of raw material companies listed on the Indonesia Stock Exchange from 2021 to 2024. This study used quantitative methods and purposive sampling techniques to analyze 61 sample companies, which were tested through panel data regression with STATA 17. The results showed that sales growth and non-debt tax shields had a positive effect on capital structure, while cash flow volatility had a negative effect. Based on the research findings, it is recommended that companies maintain stable sales growth and optimally manage non-debt tax shields, as these have been shown to improve capital structure. Managing cash flow volatility is necessary to reduce reliance on debt and financial risk. Tangible assets did not affect capital structure, indicating that tangible assets are not considered in financing decisions.